VISUAL WOMEN COMMUNICATION CAREER IN PHOTO FASHION - Arzi Darwan; Yanto yanto; Bayu Risdiyanto (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
This study aims to determine the how visual communication of career women in fashion photos on Instagram. This research is a qualitative descriptive study using data collection and analysis techniques through observation, interviews, and documentation. Presentation of data involves various steps to organize and process data a career woman (subject) in a fashion photo on instagram social media, so as all the data is analyzed thoroughly involved in a single unit. The existence of shared photos by the women's career in media instagram is a real form of visual communication from them and have specific purposes. Research results show that from several photos of women fashion career researchers set as the data to be analyzed by Researchers there are different meanings in each of the photo, but Researchers assume that this is a career woman Local Brand who is able to show themessages separate from each photo fashion up to date in their instagram social media.